Using development oriented equity investment as a tool for restructuring transition banking sectors - Meigas, Helo (Policy research working paper, 2001)
Development-oriented equity investment, undertaken in the context of World Bank projects, can assist in promoting sound banking systems, especially through its positive impact on bank governance. This was the experience of Swedfund Financial Markets that made equity investment in banks in the Baltic republics of Estonia, Latvia, and Lithuania